O discurso da notícia e a representação da identidade de gênero feminino nos crimes passionais - Oliveira, Édson Correia de (2010)
The aim of this thesis is to present a discourse analysis of press media in order to investigate how this discourse within a historical and social context, reproduce or change social values and ideologies from the perspective of gender relations, specifically in the stories of crimes of passion. For this, we selected four cases of crimes of passion of great media coverage from the 1970's and the news published by the newspaper Folha de S. Paulo in the two days following the crimes. The thesis is situated in the field of discourse analysis and is based mainly on studies of Teun A. Van Dijk, whose goal is to analyze the structure of the news and its processes of production and reception related to social practices and ideologies of those who produce in a given social context. The news discourse in society has a handler function, because it is produced by an organization that has a specific form of public communication that plays to the society what is in their interest and thus directs the reader to understand this particular speech, and thus manipulation is accomplished, which leads to hegemony or social change. The newspaper Folha de S. Paulo, in the news coverage of crimes of passion analyzed, acted in accordance with the values that were socially acceptable in every season, now promoting the hegemony, now promoting change